Reconstruction of the Palmar Defect of the Hand with a Sensory Medial Plantar Artery Flap - Li, Jiayu; Luo, Xuchao; Zou, Yonggen (Frontiers in Surgery, 2022)
Background: There are many approaches to repair palmar defect of hand , but due to the complex tissue structure, versatile functions and high restoration demands, the repair of palmar defect of hand has always been a difficult task. Choice of suitable flaps to repair this kind of injury is always a tough challenge for the reconstructive surgeon because of the limitation of number of arteries in the recipient hand and high restoration demands. The sensory medial plantar artery flap is considered as the ideal choice to repair the palmar defect of hand. Based on this technique, in the current study , we used the free sensory medial plantar artery flap to reconstruct the palmar defect of hand and acquired satisfactory results. The purpose of this study was to review the use of sensory medial plantar artery flap for the reconstruction of palmar defect of hand. Method: From January 2019 to December 2020, nine patients with palmar defect of hand underwent extremity reconstruction by the sensory medial plantar artery flap. The indications for this surgery were the palmar defect of hand need to be reconstructed and both anterior and posterior tibial arteries are free-flowing. Patients who have systemic diseases such as diabetes millitus, vascular diseases, heavy smoking histories and injuries of donor site were ruled out from the surgery. Results: Nine patients were successfully treated by sensory medial plantar artery flap with a mean age of 39.44 years. Five of the patients were male and the others were female, and 7 cases were caused by machine crush, and the other 2 cases were caused by thermal injury. All flaps survived completely, and all of the donor sites were healed well in one stage, except for one case of ischaemic skin necrosis due to tight sutures, which healed well after suture removal. Conclusion: Our experience showed that free sensory medial plantar artery flap was an alternative option for one-stage reconstruction of soft-tissue defect in the palm of hand. This flexible approach not only repair the soft-tissue defect, but also offered a satisfactory recovery of sensory of palm with minimal donor site morbidity.